Scroll, feel, buy: How social presence and FOMO shape impulsive and repeat purchases - Rika Promalessy; Ahmad Fauzan Fathoni; Dian Puspita Novrianti; T. Saipul Hadi (Journal of Applied Business Administration, 2026)
This study aims to analyze the influence of social presence and fear of missing out (FOMO) on consumer impulsive buying and repurchase intention on e-commerce platforms in Indonesia. The research is grounded in Stimulus–Organism–Response (S-O-R) Theory, which posits that environmental stimuli (social presence and FOMO) affect internal psychological states (impulsive buying) that subsequently drive behavioral responses (repurchase intention). The study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 157 active marketplace users in Indonesia. The data were analyzed using Structural Equation Modeling (SEM) with a variance-based approach (PLS-SEM) to examine both direct and indirect (mediating) effects among variables. The results indicate that social presence and impulsive buying have a significant positive effect on repurchase intention, particularly within the context of social media interaction and digital promotional strategies. Meanwhile, FOMO does not directly influence repurchase intention. However, impulsive buying significantly mediates the relationship between social presence and FOMO with repurchase intention, suggesting that both variables first stimulate impulsive buying behavior, which subsequently enhances repurchase intention. This research contributes theoretically by extending the application of Social Presence Theory and S-O-R Theory in the context of e-commerce consumer behavior in Indonesia. Practically, the findings provide strategic implications for e-commerce platforms and digital marketers to strengthen interactive features and social cues that enhance consumers’ emotional engagement and stimulate impulsive buying to increase repurchase intention.